Repatriates' job dimensions, career ambition, career expectation, and work adjustment in the Gulf Cooperation Council countries - Ali Aljofan; Anees Janee Ali (Administrative Sciences, 2022)
Gulf Cooperation Council (GCC) countries have seen a significant increase in the number of expatriated students since 2005; despite the high rates, adequate examinations of the lived experiences of students repatriating to the region are lacking. This study aimed to examine the job role determinants of work adjustment among repatriated students in the GCC. It examined the mediating effects of career ambition and the moderating effect of career expectation on repatriates' work adjustment. Data from 317 employed repatriates were gathered through an online survey. SPSS and Smart PLS 3.0 were used to analyze the data. Findings showed that repatriates' job roles are positively correlated with their work adjustment, except for role discretion. Career ambition and career expectation have positively impacted repatriates' work adjustment. However, repatriates' lived experiences from the GCC area have not been empirically documented, particularly from those adjusting to work conditions. Little is known about the influences of career ambition and career expectations on repatriates' work adjustment, how individuals experience their job roles, and what effect those roles have on work adjustment outcomes. This research offered an in-depth understanding of the influence of job roles on repatriates in the GCC, which can be utilized by repatriates and organizations to ensure better adjustment.
Keywords: 350; career ambition; career expectation; job roles; repatriates; work adjustment